2016
DOI: 10.3389/fmicb.2015.01491
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Control of Hepatitis B Virus Modulates the Outcome of Infection

Abstract: Epigenetic modifications are stable alterations in gene expression that do not involve mutations of the genetic sequence itself. It has become increasingly clear that epigenetic factors contribute to the outcome of chronic hepatitis B virus (HBV) infection by affecting cellular and virion gene expression, viral replication and the development of hepatocellular carcinoma. HBV persists in the nucleus of infected hepatocytes as a stable non-integrated covalently closed circular DNA (cccDNA) which functions as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
(88 reference statements)
1
36
0
1
Order By: Relevance
“…We demonstrated that one third of the CpG islands within the cccDNA region were methylated independently of the presence of mutations. Our results are in agreement with previous studies showing that cccDNA is a target for methylation (Vivekanandan et al, 2010;Koumbi et al, 2015). CccDNA methylation was accompanied by increased levels of cellular DNMT1 expression and the recruitment of DNMT1 onto cccDNA.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We demonstrated that one third of the CpG islands within the cccDNA region were methylated independently of the presence of mutations. Our results are in agreement with previous studies showing that cccDNA is a target for methylation (Vivekanandan et al, 2010;Koumbi et al, 2015). CccDNA methylation was accompanied by increased levels of cellular DNMT1 expression and the recruitment of DNMT1 onto cccDNA.…”
Section: Discussionsupporting
confidence: 94%
“…The methylation of episomal cccDNA in human tissue of CHB patients has been associated with impaired cccDNA mRNA synthesis capability and suppressed viral gene expression (Guo et al, 2009;Vivekanandan et al, 2010;Koumbi et al, 2015). It has been reported that DNMT1, DNMT2 and DNMT3 expression is upregulated in response to HBV, leading to viral methylation and decreased viral replication (Liu et al, 2009;Vivekanandan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific microRNAs, reported to be associated with various aspects of hepatitis B biology were classified and their role in multiple aspects related to HBV was defined (Sarkar and Chakravarty 2015). Epigenetic changes induced by the HBx protein include aberrations in DNA methylation, post-translational modification of histones, microRNA expression, and epigenetic control of HBV covalently closed circular DNA (cccDNA) (Koumbi and Karayiannis 2015;Tian and Ou 2015;Tian et al 2013). Single-nucleotide polymorphisms (SNPs) in the genes encoding miR-146a and miR-196a-2 influence susceptibility to HCC from HBV infection ).…”
Section: Additional Informationmentioning
confidence: 99%
“…Hepatitis B virus‐induced epigenetic alterations represent novel therapeutic targets for the prevention of HBV‐associated HCC development and progression. DNA methylation and post‐translational histone modifications are the most studied epigenetic marks altered by viral infections that can be medically modified using so‐called epidrugs. To date, malignancy remains to be the pivotal domain for the clinical implication of epidrug treatments in humans .…”
Section: Future Hepatitis B Treatment Optionsmentioning
confidence: 99%